2021
DOI: 10.3389/fenrg.2021.734288
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of a Concentrating Solar Power Plant Using Redox-Active Metal Oxides as Heat Transfer Fluid and Storage Media

Abstract: We present results for a one-dimensional quasi-steady-state thermodynamic model developed for a 111.7 MWe concentrating solar power (CSP) system using a redox-active metal oxide as the heat storage media and heat transfer agent integrated with a combined cycle air Brayton power block. In the energy charging and discharging processes, the metal oxide CaAl0.2Mn0.8O2.9-δ (CAM28) undergoes a reversible, high temperature redox cycle including an endothermic oxygen-releasing reaction and exothermic oxygen-incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Eng. 491, 353-363. doi:10.13336/j.1003-6520.hve.20211326 Zhang, D., Yun, Y., Wang, X., He, J., and Dong, H. (2021). Economic dispatch of integrated electricity-heat-gas energy system considering generalized energy storage and concentrating solar power plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eng. 491, 353-363. doi:10.13336/j.1003-6520.hve.20211326 Zhang, D., Yun, Y., Wang, X., He, J., and Dong, H. (2021). Economic dispatch of integrated electricity-heat-gas energy system considering generalized energy storage and concentrating solar power plant.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2019) analyzed the influences of wind power uncertainty on optimal dispatch and put forward a stochastic model for the combination of the CSP stations and wind farms according to the simulation results. In the work of Zhang G. et al (2021), CSP stations were introduced as cogenerated units and a multi-dispatch method for the RIES was proposed. The results show that the participation of CSP stations can reduce operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…The present status and future prospects of solar thermochemical fuels show potential commercial viability in the near future [23,24]. Techno-economic studies and lifecycle analyses of large-scale thermochemical plants have also confirmed the environmental benefits and favorable cost prospects of such solar technologies [25][26][27][28][29][30][31][32][33]. cations, including: (i) solar thermochemical fuel generation from water/CO2-splitting redox processes, (ii) ammonia synthesis based on chemical looping cycles, (iii) solar thermochemical energy storage for off-sun continuous processing, and (iv) thermochemical air separation/oxygen pumping for gas purification, while focusing on the latest advances in the research field of redox materials and related solar thermochemical processes.…”
Section: Introductionmentioning
confidence: 92%
“…As a specific use case, we focus on the discovery of new solar thermochemical (STCH) water splitting oxides, widely considered a promising route for renewable hydrogen production. [37][38][39] DFT investigations play a critical role in understanding these materials and helping to guide experiments, [40][41][42][43][44] but can only be accomplished on a limited scale. Due to the complexity of the associated vacancy defect calculations using DFT, approximately one year's work was required to build our training database (⇠ 200 host oxide compounds consisting of ⇠1500 unique defects).…”
Section: Introductionmentioning
confidence: 99%